Patient-centered oncosurgical planning with cancer models in subspecialty education. (June 2021) - Guler, Ezgi; Ozer, Mehmet Asim; Bati, Ayse Hilal; Govsa, Figen; Erozkan, Kamil; Vatansever, Safa; Ersin, Muhtar Sinan; Elmas, Nevra Zehra
Abstract: Background: A fundamental aspect of oncosurgical planning in organ resections is the identification of feeder vessel details to preserve healthy organ tissue while fully resecting the tumors. The purpose of this study was to determine whether three-dimensional (3D) cancer case models of computed tomography (CT) images will assist resident-level trainees in making appropriate operative plans for organ resection surgery. Methods: This study was based on the perception of surgery residents who were presented with 5 different oncosurgical scenarios. A five-station carousel including cases of liver mass, stomach mass, annular pancreas, pelvic mass and mediastinal mass was formed for the study. The residents were required to compare their perception level of the cases with their CT images, and 3D models in terms of identifying the invasion of the mass, making differential diagnosis and preoperative planning stage. Results: All residents have given higher scores for models. 3D models provided better understanding of oncopathological anatomy and improved surgical planning. In all scenarios, 70–80% of the residents preferred the model for preoperative planning. For surgical choice, compared to the CT, the model provided a statistically significant difference in terms of visual assessment, such as tumor location, distal or proximal organotomy (p:0.009). In the evaluation of presacral mass, the perception of model was significantly better than the CT in terms of bone-foramen relationship of chondrosarcoma, its origin, geometric shape, localization, invasion, and surgical preference (p:0.004). The model statistically significantly provided help to evaluate and prepare the case together with the colleagues performing surgery (p:0.007). Commenting on the open-ended question, they stated that the tumor-vessel relationship was clearly demonstrated in the 3D model, which has been very useful. Conclusions: With the help of 3D printing technology in this study, it is possible to implement and evaluate a well-structured real patient scenario setup in cancer surgery training. It can be used to improve the understanding of pathoanatomical changes of multidisciplinary oncologic cases. Namely, it is used in guiding the surgical strategy and determining whether patient-specific 3D models change pre-operative planning decisions made by surgeons in complex cancer mass surgical procedures. Highlights: To evaluate a well-structured real patient scenario setup for cancer surgery training. A five-station carousel is formed for the study. CT and 1:1 solid models of the cases are included in each station. All subspecialties agree 3D models provided better understanding pathoanatomy and improved preplanning.